A pharmacognostic, phytochemical, and antioxidant potential of Oxalis triangularis - Sharma, S.; Bhuyan, N. R.; Mohanty, J. P. (Creative Pharma Assent, 2024)
Background: To evaluate Oxalis triangularis with pharmacognostical parameters (macroscopy, microscopy & physico-chemical analysis), phytochemical analysis, and to investigate the in-vitro antioxidant capacity of different extracts obtained. Methods: Using specific standard protocols, the following tests were performed: loss on drying, extractive value, ash value, t.s. & powder microscopy, fluorescence analysis, and phytochemical screening. The Folin-Ciocalteu technique was adopted to ascertain the amount of phenolic compounds. In-vitro antioxidant activity was evaluated using 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) & 2,2'-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging assays. Results: The extractive values varied between solvents, ranging from 1.28% (ethyl acetate) to 18.8% (water), while the ash values were 16.25% (total), 2.9% (acid insoluble), and 10.625% (water-soluble). Numerous vascular systems, lignified trichomes, and calcium oxalate crystals were visible under a microscope. Saponins, steroids, flavonoids, phenols, anthocyanins, and alkaloids were detected by phytochemical screening; glycosides were not detected. At 200 µg/ml, the phenolic concentration of the ethanolic extract was the highest, at 1151.7 ± 59.22 µg/ml. The ethanolic extract exhibited greater DPPH (IC50 = 2.403 µg/ml) and ABTS (IC50 = 22.94 µg/ml) radical scavenging activity in comparison to the aqueous extract, i.e., (DPPH, IC50= 76.67 µg/ml & ABTS, IC50= 43.52 µg/ml). In contrast, both extracts showed notable antioxidant activity. Conclusion: A comprehensive examination of Oxalis triangularis revealed a rich reservoir of bioactive chemicals, such as phenols, which make the plant rich in antioxidant properties. This may serve as a foundation for the discovery of novel medicines.